Relentless : my story of the Latino spirit that is transforming America - Miranda, Luis A.; Wolffe, Richard, 1968- (Hachette Books, 2024)
"Luis Miranda arrived in New York City from Puerto Rico in 1974 to study psychology at NYU, but he soon found himself drawn to community action, eventually working for the Department of Employment, the Board of Education, and the nonprofit Aspira, among many other organizations. In the 1980s he was a special advisor for Hispanic Affairs to Mayor Ed Koch, and he continued to serve in key roles for the Dinkins and Giuliani administrations. In 1990 Miranda became the founding President of the Hispanic Federation, one of the nation's leading Latino nonprofits. In 2000, he founded the Amber Charter School in East Harlem. As a founding partner of the MirRam Group, Miranda has consulted on a number of successful political campaigns, including the Senatorial campaigns of Hilary Clinton, Chuck Schumer, and Kirsten Gillibrand. The list of roles and positions is practically endless, but, more simply put, there is no one on the Latino, New York City, and national political scene who has the breadth of experience, passion, understanding, and storytelling charm of Luis Miranda. In "Relentless," he shares the poignant narrative of his life and career-from his early days as a radically-minded Puerto Rican activist to his decades of practical political advising and problem-solving. We experience the thrill of the ascendency of Luis's son Lin-Manuel's "Hamilton" followed several years later by the devastation of Hurricane Maria. Amid the triumphs, challenges, and ongoing hard work, Miranda examines what it all tells us about our ever-changing politics, demographics, and society"--